Strategi Kolaboratif Mahasiswa dan Masyarakat dalam Mewujudkan Desa Sehat, Bersih, dan Mandiri Ekonomi: Pengabdian - Adhitya Muhdan Hadiyan K; Andrea Difa Medina; Indra Budi Jaya; Ayu Paramitha Salsabilla; Desy Rizki Trihapsari; Fikruka Fityatun Fauziah; Fadillah Robani; Muhammad Dendy Anugerah; Nur Fitriyanti Azzahra; Shalu Syafa Islami H. Y; Syifa Aulia Putri (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Community Service Program (KKN) of Universitas Muhammadiyah Bandung in 2025 was conducted in Jambudipa Village, Cisarua District, West Bandung Regency. The program aimed to raise public awareness of health, promote better environmental management, and strengthen Micro, Small, and Medium Enterprises (MSMEs) in obtaining business legality. The methods included observation, surveys, discussions, socialization, training, mentoring, and monitoring carried out over one month, from August 6 to September 6, 2025. The results showed improved community knowledge regarding stunting prevention, the role of integrated health posts, and access to free medical services. In environmental aspects, the community began practicing waste segregation and applying biopore technology to manage organic waste. In the economic sector, MSME actors received assistance in obtaining Business Identification Numbers (NIB) and free halal certification. In conclusion, this program contributes to building a healthy, clean, and economically independent village through collaborative approaches between students, village authorities, and the community. Program sustainability through continuous mentoring and support is essential to ensure that the outcomes serve as a foundation for Jambudipa Village’s long-term sustainable development.